Facile Synthesis of Luminescent AgInS 2-ZnS Solid Solution Nanorods - Yang, Xuyong (2016)
Highly luminescent semiconducting AgInS2–ZnS solid solution nanorods are successfully prepared by a facile one-pot solvothermal method. The resulting solid solution nanorods with length of 32 ± 5 nm are formed by fast growth of the AgInS2-rich solid solution head, followed by slow growth of the ZnS-rich solid solution tail. Photoluminescence studies on the solid solution nanorods reveal strong photoluminescence with peak emission wavelengths tunable from 650 to 700 nm.